Reynoutria japonica Houtt for Acute Respiratory Tract Infections in Adults and Children: A Systematic Review - Wang, Zhi-Jie; Trill, Jeanne; Tan, Lin-Lin; Chang, Wen-Jing; Zhang, Yu; Willcox, Merlin; Xia, Ru-Yu; Jiang, Yue; Moore, Michael; Liu, Jian-Ping; Hu, Xiao-Yang (Frontiers in Pharmacology, 2022)
Introduction: Respiratory tract infections (RTIs) are the a major causes of morbidity and mortality in some high-risk groups including children and older adults. There is evidence that Chinese herbal medicine has an effect on RTIs. Fallopia japonica (F. japonica), a commonly used Chinese herbal medicine, has a high content of resveratrol and glycosides. In traditional Chinese medicine theory, F. japonica has the effect ofn clearing heat in the body, improving blood and qi circulation, eliminating phlegm, and relieving cough, so it may have an effect on RTIs. Methods: This systematic review was registered under PROSPERO CRD42020188604. Databases were searched for randomized controlled trials ofn F. japonica as a single herb, or as a component of a complex herbal formula for RTIs. Quality of methodology was assessed by two reviewers independently using the Cochrane Risk of Bias Tool. The primary outcome was symptom improvement rate. The secondary outcome measures were fever clearance time, Murray lung injury score and incidence of adverse effects. The extracted data were pooled and meta-analysed by RevMan 5.3 software. Results: Eight RCTs with 1123 participants with acute RITIs were included in this systematic review, and all the RCTs used F. japonica as part of a herbal mixture. Only one included trial used F. japonica in a herbal mixture without antibiotics in the treatment group. The findings showed that herbal remedies that included F. japonica could increase the symptom improvement rate (RR 1.14, 95% CI [1.09, 1.20], I2=0%, P<0.00001, n=7 trials, 1013 participants), shorten fever duration, reduce Murray lung injury score and did not increase adverse events (RR 0.33, 95% CI [0.11, 1.00], I2=0%, P=0.05, n=5 trials, 676 participants). Conclusion: There is limited but some evidence that F. japonica as part of a herbal mixture may be an effective and safe intervention for acute RTIs in clinical practice. In future studies it would be preferable to evaluate the effectiveness and safety of using F. japonica without antibiotics for acute RTIs.